Optimizing the cross‐flow nanofiltration process for chromium (VI) removal from simulated wastewater through response surface methodology. Issue 5 (24th April 2015) - Anupam, Kumar; Sikder, Jaya; Pal, Sayan; Halder, Gopinath
Abstract : Experimental and statistical investigations on the removal of chromium (VI) from simulated wastewater over the influence of different parameters viz. pH, cross flow rate, and transmembrane pressure were carried out in cross‐flow nanofiltration through central composite response surface design. A satisfactory prediction second order regression model was developed and analysis of variance (ANOVA) showed a high coefficient of determination with R 2 value of 0.9820. The maximum chromium (VI) rejection of 0.9893 and permeate flux of 38 L/h were achieved at optimum parametric conditions of pH 11, cross flow rate 700 L/h and transmembrane pressure 10 bar. The results indicate that the chromium (VI) rejection strongly depends not only on linear and square effects of pH, cross flow rate, and transmembrane pressure but also on interaction effects of pH and transmembrane pressure as well as cross flow rate and transmembrane pressure. The study reveals that the nanofiltration process at the optimal conditions could lead to a significant result in removal of chromium (VI) from wastewater. © 2015 American Institute of Chemical Engineers Environ Prog, 34: 1332–1340, 2015